2022
DOI: 10.12688/f1000research.125551.2
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy on COVID-19 and COVID-19 vaccinations in Indonesia

Abstract: Introduction: Health literacy on the coronavirus disease 2019 (COVID-19) affects people’s capability to ascertain their health and health care quality during the pandemic. The objective of this study was to determine the levels of health literacy about COVID-19 vaccines and vaccinations (Vaccines and Vaccinations literacy-VL) in the Indonesian adult general population, assessing the perceptions of the respondents about current adult immunization and beliefs about vaccinations in general, and analyzing correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In this study, we found that people’s opinion showed on this particular social media is arguably correlated with their literacy on the issue. 52 It might be affected by the ambience of social environment and information percepted at a certain period.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that people’s opinion showed on this particular social media is arguably correlated with their literacy on the issue. 52 It might be affected by the ambience of social environment and information percepted at a certain period.…”
Section: Resultsmentioning
confidence: 99%
“…Essa pesquisa sublinha a necessidade de abordar as lacunas de conhecimento e a desinformação para melhorar as taxas de vacinação nas minorias e excluídas 18 . O letramento em vacina mostra de maneira positiva que a educação em saúde desempenha um papel crucial na promoção da vacinação em todo o mundo 33 . Ressalta-se neste contexto como o letramento vacinal pode influenciar as decisões em uma variedade de contextos culturais, na qualidade de vida e nos indicadores de saúde 34 .…”
Section: Discussionunclassified
“…(2020) study literacy programs. Media literacy research has also illuminated how the COVID-19 pandemic affected digital media (Kalanjati et al 2022). Few studies have examined media literacy in adolescents, especially high schoolers.…”
Section: Introductionmentioning
confidence: 99%